Efficacy of a new immunonutrition formula with extra virgin olive oil in the reduction of complications in surgeries of upper digestive tract tumors - Villar-Taibo, Rocío; Vidal-Casariego, Alfonso; Santamaría-Nieto, Alicia; Cantón-Blanco, Ana; Crujeiras, Ana B.; Lugo Rodríguez, Gloria; Rodríguez-Carnero, Gemma; Pita Gutiérrez, Francisco; Fernández Pombo, Antía; Díaz-López, Everardo; Román Eyo, Andrea; Rodríguez Lavandeira, Uxía; et al. (Frontiers in Nutrition, 2024)
Background: to demonstrate whether a nutritional supplement enriched with arginine, nucleotides, omega-3 fatty acids, and extra virgin olive oil reduces postoperative complications in patients with tumours in the upper digestive tract. Methods: a randomised, controlled, double-blind, multicentre clinical trial, in which a new immunomodulatory formula with extra virgin olive oil was compared with a standard isoprotein and isoenergetic formula. Patients with gastric, esophageal or biliopancreatic tumours were recruited to receive two units of immunomodulatory formula or control, five days before the surgical intervention. Results: 119 patients were recruited. There was a significant reduction in the number of reinterventions (7.7 vs. 20.4%; p = 0.044) in the intervention group. There was a significant reduction in the development of fistulas in patients with phase angles >5.7º. Also, there were fewer readmissions after biliopancreatic surgeries (0.0 vs. 100%; p = 0.014). The length of hospital stay was similar between groups; however, with the immunomodulatory formula, the patients exhibited greater phase angles at the end of follow-up. Conclusions: the immunomodulatory formula with extra virgin Con formato: Español (España) 2 olive oil administered five days before surgery for stomach, esophageal and biliopancreatic tumours improved cellular health and reduced postoperative complications.